If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 + -4x = 16 + 11x Solving 46 + -4x = 16 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 46 + -4x + -11x = 16 + 11x + -11x Combine like terms: -4x + -11x = -15x 46 + -15x = 16 + 11x + -11x Combine like terms: 11x + -11x = 0 46 + -15x = 16 + 0 46 + -15x = 16 Add '-46' to each side of the equation. 46 + -46 + -15x = 16 + -46 Combine like terms: 46 + -46 = 0 0 + -15x = 16 + -46 -15x = 16 + -46 Combine like terms: 16 + -46 = -30 -15x = -30 Divide each side by '-15'. x = 2 Simplifying x = 2
| 2(6c-2)+8c+6= | | 64-48= | | X^2y^4-81x^2=0 | | fx=9 | | 14x-8+6x=6(5x-3)+5 | | 11(k-1)=7(k-0.25) | | 2u^4+24u^3+72u^2=0 | | (-2/3)d=8 | | x^2+x-21=-6x-3 | | 2x-2=6x-4 | | 7p=27 | | 4-4x+5x=3x | | 5x^5+7x^4+70x^3+98x^2-160x-224=0 | | 12v^3+4v^2-40v=0 | | 9x-10+6x=4(6x-4)+3 | | (x-2)(x-10i)(x+10i)=0 | | (5)(13)t=-9 | | -56=-15m+m^2 | | 2x^2-4n-70=0 | | 12.6x-2.3x=206 | | -16t+80t+384=0 | | fx=3x+3 | | a^2+7a-9=-3a+6a | | -1/4x=6=2/3x=28 | | -15m+m^2+56=0 | | w^2-3w-208=0 | | Y=-2.5+150 | | -1.5=x/-0.8 | | Fx=4x+6 | | 2x+3y=8fory | | 2x-5+35+90=180 | | 3x^2-14=x^2+3x |